The Designing of Teaching Materials by Using Mnemonic Music Techniques to Strengthen Vocabularies Memorizing - Ningsih, Wiwik Prasetiyo; Hamid, M. Abdul; Rosyidi, Abdul Wahab; Hamdy, Mohammad Zainal (Arabiyatuna: Jurnal Bahasa Arab, 2024)
This paper discusses about learning vocabulary. The vocabulary is an important element of the Arabic language that must be mastered by all students of the Arabic language. But sometimes students feel bored due to difficulty of vocabulary memorization. This problem requires innovation by vocabulary teachers to solve this problem. The researcher found that students in Darul Lughah wal Qur’an College had difficulty memorizing vocabulary, which led the researcher to integrate mnemonic music techniques into vocabulary learning to facilitate the students' memorization of vocabulary. The Mnemonic music came to help them in memorizing the vocabulary easily and with strong memory. The aims of this research are first, to understand how to design teaching materials by using mnemonic music to strengthen vocabularies memorizing, second, to understand the specifications of the teaching materials that developed, and to determine the effectiveness of teaching materials that developed. This research use qualitative and quantitative approach. The method of this research is research and development. The researcher use interview technique, observation technique, questionnaire technique, and test technique to collect the data.  The result of this research is that this research is carried out using the ADDIE model according to Dick and Carrey, its mean analysis, design, development, implementation and evaluation. The specifications of the the teaching materials in this research is that they are developed by using mnemonic music technique which is consists of cover, aims of learning, chapters, new vocabularies, and many exercises of vocabularies. This material consist of 24 chapters which is developed by using mnemonic music technique. The result of the product experiment is 10,4>2,80>2,08: t. >ts0,01>0,05 indicates that these developed teaching materials are effective in strengthening vocabulary memorization.